Structural validity and internal consistency of the Patient Centred Assessment Method in a primary care setting in a Japanese island area: a cross-sectional study. Issue 6 (28th June 2022) - Sugiyama, Yoshifumi; Mutai, Rieko; Yoshimoto, Hisashi; Horiguchi, Ryoko; Yoshida, Shuhei; Matsushima, Masato
Abstract : Objectives: The objective of this study was to examine the structural validity and internal consistency of the original English version of the Patient Centred Assessment Method (PCAM) in a primary care setting in a Japanese island area. Design: Cross-sectional study. Setting: A clinic on a remote island in Okinawa, Japan, that provides general outpatient and 24-hour emergency services. Participants: This study included 355 patients who visited Tarama Clinic from 1 April 2018 to 30 June 2018, were aged ≥20 years, lived in Tarama Village and had decision-making capacity. Main outcome measures: Patient complexity scored by the PCAM. Results: The mean (SD) PCAM score was 21.4 (5.7). The distribution was skewed to the right and there were no ceiling and floor effects. Confirmatory factor analysis found that the previously reported two-factor and three-factor structures did not show a good fit (root mean square error of approximation 0.18 and 0.16, comparative fit index 0.83 and 0.89 and standardised root mean square residual 0.14 and 0.11, respectively). Exploratory factor analysis revealed a new two-factor structure: 'Biomedical complexity' and 'Psychosocial complexity'. The Cronbach's alpha values for the total PCAM score, the 'Biomedical complexity' factor, and the 'Psychosocial complexity' factor were 0.81, 0.82 and 0.74, respectively. Conclusions: In this study, confirmatory factor analysis found that the data did not fit sufficiently using the previously reported two-factor and three-factor structures. Instead, exploratory factor analysis revealed a new two-factor structure, for which the Cronbach's alpha values exceeded the threshold level. Therefore, the structural validity and internal consistency of the English version of the PCAM were verified in a primary care setting in a Japanese island area.